Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijms222312761
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Cell-Intrinsic DNA Damage Response by the Innate Immune Machinery

Abstract: Maintenance of genomic integrity is crucial for cell survival. As such, elegant DNA damage response (DDR) systems have evolved to ensure proper repair of DNA double-strand breaks (DSBs) and other lesions that threaten genomic integrity. Towards this end, most therapeutic studies have focused on understanding of the canonical DNA DSB repair pathways to enhance the efficacy of DNA-damaging therapies. While these approaches have been fruitful, there has been relatively limited success to date and potential for si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 122 publications
0
8
0
Order By: Relevance
“…42 Furthermore, DDR can trigger an innate immune response that inhibits viral proliferation. 26,43 Therefore, further investigations into the role of DDR in alphaherpesvirus proliferation are needed to identify potentially therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Furthermore, DDR can trigger an innate immune response that inhibits viral proliferation. 26,43 Therefore, further investigations into the role of DDR in alphaherpesvirus proliferation are needed to identify potentially therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that H2AX phosphorylation and DNA damage kinase activity are dispensable for HSV‐1 replication 42 . Furthermore, DDR can trigger an innate immune response that inhibits viral proliferation 26,43 . Therefore, further investigations into the role of DDR in alphaherpesvirus proliferation are needed to identify potentially therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the HPV18 and HPV16 E2 proteins is also sufficient to downregulate STING mRNA levels along with the several other innate immune genes [95,99]. The cGAS-STING pathway plays a critical role in the response to damaged DNA that is mislocalized to the cytoplasm as well as DNA within micronuclei [100,101]. HR HPVs induce DNA damage and require activation of DNA damage response pathways for viral replication [14,25].…”
Section: Interference With Ifn Inductionmentioning
confidence: 99%
“…Radiotherapy is an important component of the multi-modality treatment for metastatic NSCLC, with ~50% of NSCLC patients undergoing radiotherapy either for a curative or palliative intent [ 105 ]. Radiotherapy kills tumor cells either by directly inducing DNA damage, which leads to cell death as well as increases anti-tumor immune response [ 106 ] or by indirectly altering tumor vasculature [ 107 ]. As said before, a large fraction of miRNAs associated with radiotherapy was downregulated in radioresistant samples and vice versa upregulated in radiosensitive ones, for example:(i) miR-218-5p overexpression restored the sensitivity of radiation-resistant cells through direct regulation of PRKDC, a member of the non-homologous end-joining pathway in the DNA double-strand break repair response [ 108 ]; (ii) rescue of miR-126-3p expression increased radiation-induced apoptosis by inactivation of the PI3K/AKT signaling [ 109 ].…”
Section: Relevant Sectionsmentioning
confidence: 99%